Wet Cupping Therapy to The Arterial Baroreflex Sensitivity on Hypertensive Elderly - Fadli, Fadli; Fatmawati, Fatmawati (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Wet cupping therapy can remove toxins and prevent atherosclerosis. This process will stimulate the sensitivity of the arterial baroreflex which will stimulate a decrease in blood pressure. This is to determine the impact of cupping therapy on the sensitivity of arterial baroreflex with blood pressure indicators in the elderly suffering from hypertension. Quasi-experimental research using pre and post-test and group control design approaches. The sampling technique was simple random sampling, consisting of 21 respondents which was carried out from January to April 2020. The statistics used the General Linear Model Repeated Measures (GLM-RM) test. There was a significant difference between the sensitivity of arterial baroreflex on blood pressure measurement indicators before and after 2 weeks of follow-up period at systolic BP p-value = 0.000 (24.29 ± 8.11 mmHg) and diastolic BP p-value = 0.001 (5.24 ± 6.02); between 2 weeks and 4 weeks at systolic BP p-value = 0.000 (10.95 ± 6.25 mmHg) and diastolic BP p-value = 0.000 (9.05 ± 6.25 mmHg); Between 4 weeks and 6 weeks there was no significant difference in the sensitivity of arterial baroreflex on the measurement indicator systolic BP p-value = 0.267 (-1.43 ± 5.73) and BP diastole p-value = 0.771 (-0.48 ± 7.40). Wet cupping therapy effectively increases the sensitivity of arterial baroreflex with an indicator of decreasing blood pressure in the elderly suffering from hypertension to a limit of 4 weeks after therapy and measurement after 6 weeks of having increased blood pressure.